Intermittent fasting reduces neuroinflammation in intracerebral hemorrhage through the Sirt3/Nrf2/HO-1 pathway - Dai, Shuhui; Wei, Jialiang; Zhang, Hongchen; Luo, Peng; Yang, Yuefan; Jiang, Xiaofan; Fei, Zhou; Liang, Wenbin; Jiang, Jianli; Li, Xia (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Inflammation contributes to the poor prognosis of intracerebral hemorrhage (ICH). Intermittent fasting (IF) has been shown to be protective against inflammation in multiple pathogenic processes. In the present study, we aimed to investigated the beneficial effects of IF in attenuating neuroinflammation and neurological deficits in a mouse model of ICH and to investigate the underlying mechanism. Methods ICH was modeled by intrastriatal injection of autologous blood and IF was modeled by every-other-day feeding in male control mice (C57BL/6), mice with and microglia specific knockout Sirt3f/f;Cx3cr1-Cre (Sirt3 cKO), and Sirt3f/f (wild-type) mice. Brain tissues and arterial blood were harvested at 1, 3, 7 and 28 days after ICH for immunohistochemistry analysis of Iba-1, DARPP-32 and HO-1, morphological analysis by HE staining and inflammatory factor release tests by ELISA. Neurological functions were approached by corner test and cylinder test. Fluorescent double-labeled staining of Iba-1 with CD16, Arg1 or Sirt3 was used to provide direct image of co-expression of these molecules in microglia. TUNEL, cleaved caspase-3 and Nissl staining was performed to evaluate cellular injuries. Results IF alleviated neurological deficits in both acute and chronic phases after ICH. Morphologically, IF enhanced hematoma clearance, reduced brain edema in acute phase and attenuated striatum atrophy in chronic phase. In addition, IF decreased the numbers of TUNEL+ cells and increased Nissl+ neuron number at day 1, 3 and 7 after ICH. IF suppressed CD16+Iba-1+ microglia activation at day 3 after ICH and reduced inflammatory releases, such as IL-1β and TNF-α. The above effects of IF were attenuated by microglia Sirt3 deletion partly because of an inhibition of Nrf2/HO-1 signaling pathway. Interestingly, IF increased Iba-1+ microglia number at day 7 which mainly expressed Arg1 while decreased the proinflammatory factor levels. In mice with microglia-specific Sirt3 deletion, the effects of IF on Iba-1+ microglia activation and anti-inflammatory factor expressions were attenuated when compared with wild-type Sirt3f/f mice. Conclusions IF protects against ICH by suppressing the inflammatory responses via the Sirt3/Nrf2/HO-1 pathway.